(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, knowledge and compliance with regulatory legal documents regulating the economic sphere of the society (for example, the law-abiding behavior of tax-paying subjects of trade relations and others); understanding of causal relationships between subjects of the market economy in the field of legal and economic relations (for example, property relations, anti-corruption behavior, etc.); it is reflected that making decisions that help to satisfy economic interests in the context of the existing legal reality, etc., is the main form of economic and legal culture.